2010
DOI: 10.1504/wremsd.2010.031638
|View full text |Cite
|
Sign up to set email alerts
|

Development of SMEs through clusters: a comparative study of India, Pakistan and Sri Lanka

Abstract: Clusters evolve as a mechanism to gain competitive advantage, when industrial units come together to share knowledge and supplement each other in enhancing strengths. The phenomenon of clustering is known to have created a high degree of networking, a market focus, an ambiance of high productivity, excellence, development of skills and creativity. These in turn can lead a firm to technological innovation and its applications. Large customers prefer to source from clusters which have developed networking to mee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Klotz, Horman, Bi and Bechtel [79] have found that all tender procedures that might benefit small businesses and enterprises must be administered with adequate transparency as a means of supporting the SMME sector. Dasanyaka and Sardana [80] have found that strategic partnerships between national and provincial Governments as well as academic institutions benefit the SMME sector in terms of producing workable plans of actions. Edwards, Sengupta and Tsai [81] have argued that mentorship is critically helpful for reducing failure rate in newly established small enterprises.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Klotz, Horman, Bi and Bechtel [79] have found that all tender procedures that might benefit small businesses and enterprises must be administered with adequate transparency as a means of supporting the SMME sector. Dasanyaka and Sardana [80] have found that strategic partnerships between national and provincial Governments as well as academic institutions benefit the SMME sector in terms of producing workable plans of actions. Edwards, Sengupta and Tsai [81] have argued that mentorship is critically helpful for reducing failure rate in newly established small enterprises.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The ICT talent pool of the country has registered tremendous growth in recent years, with universities alone producing 10000 computer science graduates every year. However, this lags far behind the regional player India, which produces about 150,000 graduate professionals in its IT based institutions (Dasanayaka, 2010).…”
Section: Potential For Employmentmentioning
confidence: 99%
“…The initiative, called Virtual Exchange, is set to provide over 50,000 business leads to exporters of Pakistan, giving them access to 202 territories and countries around the globe (Mujahid 2001). However, SMEDA does not have a specified export cluster for ICT-specific products and services, and hence this SME sub-sector is largely not accounted for in its policy initiatives (Dasanayaka, 2010).…”
Section: Potential For Local Consumptionmentioning
confidence: 99%
“…At least 50 per cent of the available coir husk is used to produce coir products and the rest is used as fuel in rural areas. Subsequently, coir industry can be grown up [1]. Numerous development programs are also undertaken by the Government authorities for the improvement in quality and production of coir industry.…”
Section: Introductionmentioning
confidence: 99%